LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION IN OMPOK BIMACULATUS (BLOCK) FROM BHAVANISAGAR RESERVOIR (TAMIL NADU) - Sivakami, S (Indian Journal of Fisheries, 2011)
Length-weight relationship and relative condition in Ompok bimaculatuswere studied. Analysis of covariance of the regressions for the two sexes showedno significant difference in slopes. The value of the exponent indicated a deviationfrom the cube law. The point of inflexion in the relative condition plottedon a lengthwise basis gave the size at first maturity, especially in males. Seasonalvariations in the condition was found to be influenced by the spawning cycle.